Blindness Registers as Epidemiological Tools for Public Health Planning: A Case Study in Belize. (3rd December 2014) - Baxter, Sally L.; Wormald, Richard P.; Musa, Joan M.; Patel, Daksha
Abstract : For public eye health programs, blindness registers can be an important tool for informing service planning. This study examines how the Belize Council for the Visually Impaired (BCVI) used its blindness register data to drive several public health interventions. Cross-sectional analysis was performed for all active registrants (n = 1194 ) to determine the distribution of causes of registration according to age, sex, and geographical district. Cataract was the leading cause of registration (39.6%), followed by glaucoma (20.8%), diabetic retinopathy (10.2%), and childhood blindness (9.4%). The distribution of the causes of registration was fairly similar between men and women and across the various districts. However, in Stann Creek, whose population is largely of African descent, glaucoma exceeded cataract. For most causes, the majority of registrants were registered at age 50 or older. Follow-up was conducted four years later. Several interventions had been initiated, most notably bolstering cataract surgical services and creating screening programs for glaucoma and diabetic retinopathy. The register itself was also improved to maximize its utility for future use. While standardized surveys may be the most appropriate method of estimating population-based measures such as prevalence or incidence, the blindness register is still a valuable source of data for public health planning.